The first larval description in the genus Diaphorocera Heyden (Coleoptera: Meloidae: Cerocomini): D. chrysoprasis Fairmaire - Turco, Federica; Giulio, Andrea Di; Bologna, Marco A. (Zootaxa, 2006)
The first instar larva of Diaphorocera chrysoprasis Fairmaire, 1863, a Western Saharan species, is described and figured for the first time. Adults of D. chrysoprasis were collected in Tunisia and larvae were reared ex ovo under laboratory conditions. Both egg and triungulin are described and illustrated by SEM and light microscope. The triungulin shows a campodeiform morphology, typical of non phoretic Meloinae. From the comparison between the first instar larvae of Cerocoma, the single other genus of the tribe Cerocomini whose larvae were known, and Diaphorocera, some distinctive characters are recognised. The phylogenetic placement of the tribe Cerocomini within the family is discussed.